Mycotoxins in Mozambique: Need for a national monitoring programme - Tamele, Isidro; Hassouani, Meryem; Timba, Ilário; Guimarães, Tiago; Maia, Rui; Falé, Zizina; Vasconcelos, Vitor (South African Journal of Science, 2022)
The occurrence of mycotoxins poses a threat to public health in Mozambique, with several cases of poisoning in humans caused by aflatoxins after consumption of groundnuts and maize reported before 1975. Over time, the control and monitoring of mycotoxins in agricultural and non-agricultural food and feed seem to have dropped significantly in Mozambique. So, the objective of this review is to recommend the implementation of monitoring and control of mycotoxins and fungal development. From our review, we note that data regarding mycotoxins in Mozambique are very limited and this makes it difficult to assess the spatial and temporal occurrence of mycotoxins in Mozambique. The scarcity of data does not mean that mycotoxins do not occur in Mozambique because the few studies that are available have confirmed the presence of mycotoxins in food and feed at concentrations above permissible limits in many countries of the world. This situation indicates a need for the creation of mycotoxin monitoring programmes involving the ministries of agriculture and public health (in coordination with universities) at the national level.Significance:This review provides relevant information that can help local authorities in Mozambique to implement a mycotoxin monitoring programme.